SOCIAL MEDIA USE INTENSITY AND ADOLESCENT ANTISOCIAL BEHAVIOR: A CROSS-SECTIONAL STUDY IN SIDOARJO: Intensitas Penggunaan Media Sosial dan Perilaku Anti Sosial Remaja: Studi Cross Sectional di Kabupaten Sidoarjo - Nur Budiarti, Tamara; Andriani, Linda; Dewanti, Nisa; Rizka Rohmawati, Nina; Muthmainnah; Wagiu Basrowi, Ray; Tenrisau, Dhihram; Mohammed Ali Aldubaeiu, Haitham Taleb Salem (Jurnal Berkala Epidemiologi, 2025)
Background: Social media usage is rapidly increasing and has become integral to everyone. The increased use of social media among adolescents has generated substantial concerns regarding its potential effects on mental health disorders. Purpose: This study investigates how the intensity of social media use influences antisocial behavior. Methods: The research was conducted in Sidoarjo Regency, held from March to April 2025, as an analytical observational method with a cross-sectional design. The population consisted of adolescents aged 17 to 25, with a total sample of 384 respondents selected through simple random sampling based on defined inclusion and exclusion criteria. Variables assessed included social media usage intensity, sleep disorder, self-confidence, anxiety regarding the future, and antisocial behavior. Data were collected using a self-reporting questionnaire and path analysis. Results: Findings indicated that 21.40% of respondents had low social media usage intensity, 7.00% experienced low sleep disorder, 24.20% had high self-confidence, and 18.20% did not experience anxiety about the future. Antisocial behavior was predominantly low among respondents (69.50%). The intensity of social media use was found to influence antisocial behavior directly and indirectly. Conclusion: Adolescents in Sidoarjo Regency displayed mental health disorder symptoms such as sleep disorder, reduced self-confidence, anxiety about the future, and antisocial tendencies. These findings highlight the importance of responsible social media use education, digital literacy programs, stress management initiatives, and increased involvement from families and educational institutions to create supportive environments promoting adolescent emotional stability.